Verilog HDL design examples - Cavanagh, Joseph; CRC Press (Boca Raton, FL : CRC Press, 2017)
The Verilog language provides a means to model a digital system at many levels of abstraction from a logic gate to a complex digital system to a mainframe computer. The purpose of this book is to present the Verilog language together with a wide variety of examples, so that the reader can gain a firm foundation in the design of the digital system using Verilog HDL. The Verilog projects include the design module, the test bench module, and the outputs obtained from the simulator that illustrate the complete functional operation of the design. Where applicable, a detailed review of the theory of the topic is presented together with the logic design principles including: state diagrams, Karnaugh maps, equations, and the logic diagram. Numerous examples and homework problems are included throughout. The examples include logical operations, counters of different moduli, half adders, full adders, a carry lookahead adder, array multipliers, different types of Moore and Mealy machines, and arithmetic logic units (ALUs)
chapter 1 Introduction to Logic Design Using Verilog HDL / Joseph Cavanagh -- chapter 2 Combinational Logic Design Using Verilog HDL / Joseph Cavanagh -- chapter 3 Sequential Logic Design Using Verilog HDL / Joseph Cavanagh -- chapter 4 Computer Arithmetic Design Using Verilog HDL / Joseph Cavanagh.
Keywords: Digital electronics -- Computer-aided design; Logic design; Verilog (Computer hardware description language).